1992
DOI: 10.1099/00222615-36-3-172
|View full text |Cite
|
Sign up to set email alerts
|

Use of contour-clamped homogeneous electric field (CHEF) electrophoresis to type methicillin-resistant Staphylococcus aureus

Abstract: Summary. Strains of methicillin-resistant Staphylococcus aureus (MRSA) from Australia and the UK were compared by digesting their chromosomal DNA with the low-frequencycutting restriction enzyme SmaI and separating the restriction fragment length polymorphisms (RFLPs) by contour-clamped homogeneous electric field (CHEF) electrophoresis. The numbers of restriction fragments produced were in the range 14-17 and the sizes of the bands were 7-700 kb. Generally, the results confirmed previous conclusions based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Contour-clamped homogeneous electric field analysis (32) indicated that the gene mapped to the SmaI A fragment of chromosomal DNA from 209P (data not shown).…”
Section: To 11 In the Translated Protein (T-e-n-k-g-s-s-q-p-k) Werementioning
confidence: 99%
“…Contour-clamped homogeneous electric field analysis (32) indicated that the gene mapped to the SmaI A fragment of chromosomal DNA from 209P (data not shown).…”
Section: To 11 In the Translated Protein (T-e-n-k-g-s-s-q-p-k) Werementioning
confidence: 99%
“…Chromosomal DNA was isolated as described previously [10]. The blocks were treated with Sma I restriction endonuclease (New England Biolab) according to the manufacturer's instructions.…”
Section: Chromosomal Dna Isolationmentioning
confidence: 99%
“…Several molecular epidemiological techniques have been used to type MRSA isolates. These include plasmid pro®le [8], restriction fragment-length polymorphism (RFLP) of plasmids [6,9], pulsed-®eld gel electrophoresis (PFGE) of Sma I-digested chromosomal DNA [10,11] and Southern hybridisation with various probes [12]. A combination of different methods can provide good strain discrimination [6,7,13].…”
Section: Introductionmentioning
confidence: 99%
“…26 Briefly, MRSA were grown to late log phase, washed and resuspended in 50 mM EDTA buffer to a concentration of c. 6 x lo5 cells/ml. The cells were then suspended in agarose 1 YO and lysed.…”
Section: Methodsmentioning
confidence: 99%